2017
DOI: 10.21608/ejoh.2017.1100.1008
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Foliar Sprayings of Salicylic Acid with Elevated Concentrations Enhance Growth, Yield and Fruit Quality of Strawberry (Fragaria x ananassa Duch. cv. Festival) Plants

Abstract: SALICYLIC ACID regulates several physiological and biochemical processes in plants. The previous studies on strawberry used salicylic acid with low concentrations varied from 0.5 mM to 2.0 mM which was sprayed once, twice or three times. The highest concentrations of salicylic acid with the maximum times of applications gave the highest values of growth and yield parameters. To study the effect of frequent foliar sprayings of salicylic acid with elevated concentrations (0.0, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, or 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…On the other hand, SA and P treatments had a significant influence on the plantlets of all tested cultivars of tbr and accessions of chc under examined high stress level. All of the aforementioned is consistent with numerous studies that have been conducted in this regard [66,67]. SA performs a variety of important physiological mechanisms in plants, including increasing nutrient uptake and the level of chlorophyll and carotenoid pigments, modifying the activities of some enzymes, and preserving the cell membrane's integrity [27,28].…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, SA and P treatments had a significant influence on the plantlets of all tested cultivars of tbr and accessions of chc under examined high stress level. All of the aforementioned is consistent with numerous studies that have been conducted in this regard [66,67]. SA performs a variety of important physiological mechanisms in plants, including increasing nutrient uptake and the level of chlorophyll and carotenoid pigments, modifying the activities of some enzymes, and preserving the cell membrane's integrity [27,28].…”
Section: Discussionsupporting
confidence: 86%
“…cv. Festival) (Youssef et al, 2017) and tomato (Solanum lycopersicum L.) (Hayat et al, 2008) foliar application of SA Figure 2. SPAD index in wheat leaves evaluated at 14, 21, 28, and 35 days after the application of treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In respect of effect of cropping periods, the amount of chlorophyll content in the leaves as expressed by SPAD values were significantly (p<0.05) higher in September-November (47.6) as compared to those in other two cropping periods (Table 1b). Youssef et al [28] found no significant effects of interaction between periods and the root-zone temperature (RZT) in chlorophyll contents. In respect to fruit number, cucumber plants of cooled RZT-22ºC and 25ºC produced more fruit number/ m 2 to the extent of 207 and 209 respectively that those at RZT-28ºC (186) and control (151) ( Table 1b).…”
Section: Growth and Yield Traitsmentioning
confidence: 99%